PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK DI SD NEGERI 20 BANTAN TENGAH - Asmawati, Sri; Karimah, Siti; Chanifudin, Chanifudin (STAI Darul Qalam Tangerang, 2023)
This research is motivated by the role of Islamic religious education teachers in overcoming the learning difficulties of students at SD Negeri 20 Bantan Tengah. The purpose of this study is to find out how the role of Islamic religious education teachers in overcoming students' learning difficulties and to find out the supporting and inhibiting factors of the role of Islamic religious education teachers in overcoming learning difficulties. The theory used in this study is the role of teachers and the learning difficulties of learners. While the method used in this study is quality with data collection through observation, interviews and documentation. The result obtained from this study is that the teacher has played his role well with the teacher required to be a facilitator and make his students like his own children. By approaching with their students, teachers can be role models for their students. To carry out its role as a teacher, teachers take a personal approach, use learning methods and media and provide guidance to students who have learning difficulties. The supporting factor of the role of this teacher is a complete school environment with decent and adequate facilities. While the inhibiting factor is the students themselves or the students themselves and the parents of these students